2021
DOI: 10.1002/ajmg.a.62377
|View full text |Cite
|
Sign up to set email alerts
|

Expanding the clinical and radiological phenotypes of leukoencephalopathy due to biallelic HMBS mutations

Abstract: Pathogenic heterozygous variants in HMBS encoding the enzyme hydroxymethylbilane synthase (HMBS), also known as porphobilinogen deaminase, cause acute intermittent porphyria (AIP). Biallelic variants in HMBS have been reported in a small number of children with severe progressive neurological disease and in three adult siblings with a more slowly, progressive neurological disease and distinct leukoencephalopathy. We report three further adult individuals who share a distinct pattern of white matter abnormality… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(14 citation statements)
references
References 36 publications
0
12
2
Order By: Relevance
“…In zebrafish, the knockdown of CLPX can be rescued through the supplementation of the heme precursor ALA (delta-amino levulinic acid) [22]. A common iron/heme-related pathway connects the two diverse clinical manifestations, given that porphyrias can progress into ataxia/leukodystrophy [23][24][25][26][27][28][29]. The relevant CLPX functions independent from CLPP were uncovered in Saccharomyces cerevisiae (where CLPP is not conserved) via a genetic screen, which showed that the CLPX ortholog activates the heme biosynthesis enzyme ALAS (5-aminolevulinic acid synthase), so CLPX deletion causes a 5-fold reduction in ALA and a 2-fold reduction in heme [30].…”
Section: Introductionmentioning
confidence: 99%
“…In zebrafish, the knockdown of CLPX can be rescued through the supplementation of the heme precursor ALA (delta-amino levulinic acid) [22]. A common iron/heme-related pathway connects the two diverse clinical manifestations, given that porphyrias can progress into ataxia/leukodystrophy [23][24][25][26][27][28][29]. The relevant CLPX functions independent from CLPP were uncovered in Saccharomyces cerevisiae (where CLPP is not conserved) via a genetic screen, which showed that the CLPX ortholog activates the heme biosynthesis enzyme ALAS (5-aminolevulinic acid synthase), so CLPX deletion causes a 5-fold reduction in ALA and a 2-fold reduction in heme [30].…”
Section: Introductionmentioning
confidence: 99%
“…Mice were housed under specific-pathogen-free conditions under a 12 h light cycle with food and water ad libitum in the central animal facility (ZFE) of the University Hospital Frankfurt. The study was conducted according to the guidelines of the Declaration of Helsinki, and approved by the Institutional Review Board of Regierungspräsidium Darmstadt (protocol code V54-19c20/15-FK/1073, date of approval Sept. 28,2016). Due to the complete infertility of CLPP-null homozygous mice of both sexes, breeding was performed simultaneously among multiple pairs of heterozygous mutation carriers, aging them under identical conditions until sacrificed for analysis.…”
Section: Animal Breeding Aging and Dissectionmentioning
confidence: 99%
“…The study was conducted according to the guidelines of the Declaration of Helsinki, and approved by the Institutional Review Board of Regierungspräsidium Darmstadt (protocol code V54-19c20/15-FK/1073, date of approval Sept. 28,2016).…”
Section: Institutional Review Board Statementmentioning
confidence: 99%
See 1 more Smart Citation
“…Monoallelic pathogenic variants in HMBS are well known to cause autosomal dominant acute intermittent porphyria (AIP) (Puy et al, 2010). In contrast, pathogenic compound heterozygous or homozygous variants in the HMBS gene have been reported in patients with progressive leukoencephalopathy-type neurological symptoms and progressive ophthalmic symptoms manifesting during childhood or adolescence (Stutterd et al, 2021). The patients with biallelic HMBS variants have neurological symptoms with spasticity, peripheral polyneuropathy, and cerebellar ataxia as well as optic nerve atrophy and hearing loss.…”
mentioning
confidence: 99%